EKSPLORASI SISTEM DAN PROSEDUR PEMBELIAN ALAT KESEHATAN : PERSPEKTIF PENGENDALIAN INTERN - Puspita, Dyah Rangga; Rahmatika, Lisa Aulia; Agustiningtias, Eka; Setiyowati, Arie Ika (STIA MALANG, 2025)
Medical equipment is vital for providing healthcare services in hospitals. To ensure that medicalequipment procurement is both effective and efficient, a strong purchasing system and robust internal controls are necessary to prevent budget deviations and misuse.This study explores the medical equipment purchasing system and procedures at RS Khusus Bedah Hasta Husada, focusing on improving internal controls. Utilizing a qualitative approach, the research involves datam collection through interviews, observations, and documentation. The analysis evaluates the purchasing system and procedures, including related functions, the documents used, record-keeping, management information needs, and procedural networks. It also assesses internal control elements such as organizational structure, authorization systems, best practices, and the quality of employees relative to their responsibilities.The study finds that the hospital's medical equipment purchasing system is generally effective.Nonetheless, there are notable weaknesses in internal controls that need to be addressed: 1) Insufficient oversight and authorization in the purchasing process as per the Budget Cost Plan (RBA), and 2) Inadequate employee training hinders the enhancement of Human Resource quality